Cerdas Bermedia Sosial dan Produktif Bagi Ibu Rumah Tangga Melalui Pelatihan Digital Marketing - Kaslam Kaslam; Riska Luneto; Andi Annur Aisyah; Nurul Huda Rahmadani (Program Studi Ilmu Politik bekerjasama Program Studi Hubungan Internasional, Universitas Islam Negeri Alauddin Makassar, 2023)
The use of the internet to market products or known as digital marketing, is currently growing very rapidly. The level of usage is in line with the presence of smartphones at very affordable prices. However, its use is actually not optimal because it is only used for social media which is not productive. Even though it can be used in entrepreneurship, especially among housewives, so that their time is more efficient. This community service activity was carried out in the form of training for 20 housewives who already have businesses, in Moncongloe Village, Maros Regency, with the theme